Desafio do Núcleo de Atenção Médica Integrada diante da necessidade de inserção de fonoaudiólogo na Rede Municipal de Saúde de Fortaleza The challenge of Núcleo de Atenção Médica Integrada in view of the need to include the speech-language pathologist in Fortaleza's Municipal Health System - Maria Emília Macedo Lopes Silva; Christina Cesar Praça Brasil; Aretuza Carla da Fonseca Regis (Universidade de São Paulo, 2010)
OBJETIVO: Demonstrar a necessidade da inserção do fonoaudiólogo na rede municipal de saúde de Fortaleza-CE, diante da elevada demanda de usuários e da escassez de serviços gratuitos de fonoaudiologia nesse município. MÉTODOS: Estudo documental, transversal e descritivo com abordagem quantitativa, realizado de julho e setembro de 2008, no qual foram analisados os documentos de atendimentos fonoaudiológicos do Núcleo de Atenção Médica Integrada da Universidade de Fortaleza (NAMI-Unifor), no período de janeiro de 2006 a dezembro de 2007. RESULTADOS: Houve predomínio de atendimento das faixas etárias de 0 e 6 anos no setor de audiologia, (22,05%); e de 0 a 10 anos no setor de fonoterapia, (58,09%). O exame audiológico mais procurado foi a audiometria (65,78%); o principal responsável pelo encaminhamento ao setor de audiologia foi o otorrinolaringologista (56,39%). No setor de fonoterapia, a linguagem foi a área com maior prevalência de atendimentos (36,99%). A terapia em grupo atingiu percentual significativo, com 37,27%, em 2007. Foi registrada queda no número de atendimentos durante o período de recesso da Universidade, devido à redução do número de alunos. CONCLUSÃO: Com um trabalho em nível de atenção primária, no que concerne à saúde da comunicação humana/deglutição, haveria diminuição de gastos públicos com o tratamento das alterações fonoaudiológicas nos demais níveis de atenção. A presença do fonoaudiólogo nas Unidades Básicas de Saúde (UBS) possibilitaria a melhoria da qualidade de vida da população em todos os ciclos de vida, além da redução da sobrecarga nos serviços gratuitos que prestam atendimento fonoaudiológico no município de Fortaleza. PURPOSE: To demonstrate the need to include the speech-language pathologist and audiologist in the municipal health system of the city of Fortaleza (Northeastern Brazil), due to the high demand of patients and the lack of public speech-language and audiology services in the city. METHODS: Documental, cross-sectional and descriptive study with a quantitative approach, developed between July and September 2008. Data were collected through the analysis of the records of the speech-language and audiology assistance provided for patients at NAMI-Unifor (The Medical Care Nucleus of the University of Fortaleza) in the period from January 2006 to December 2007. RESULTS: There was predominance of the assistance provided for the age groups between 0 and 6 years old in the audiology service (22.05%) and 0 to 10 years old in the speech-language therapy service (58.09%). The most applied audiology procedure was audiometry (65.78%), and the main professional responsible for referring patients to the audiology service was the otorhinolaryngologist (56.39%). In speech-language therapy, oral language and/or writing was the area with the highest prevalence of visits (36.99%). Group therapy reached a significant percentage: 37.27% in 2007. A fall in the number of visits during the University's recess period was observed, due to the reduction in the number of students who are responsible for the procedures. CONCLUSION: With work in the level of primary care as regards the health of human communication/deglutition, there would be a reduction in public expenses with the treatment of speech-language and audiology alterations in the other health care levels. The presence of the speech-language therapist in the Primary Care Units would help to improve the quality of life of the population across the whole life cycle, and would also reduce the burden in the public services that provide speech-language therapy in the city of Fortaleza.